Elevating the Tradition of Women Making Grilled Chili Paste as a Commercial Product to Increase Supplementary Income - Aini, Desti Nur (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
The women's community involved in SMEs (Small and Medium-sized Enterprises) in Benjor Village is a phenomenon of housewives seeking livelihoods not only out of necessity but also due to willingness, ability, and available job opportunities, as well as access to these opportunities. Such a tradition is one of the many economic activities that communities can engage in by harnessing resources that rely on ideas and knowledge as the primary factors in their economic activities. Sambal Bakar (grilled chili sauce) is a flagship product in one of the regions in Malang Regency that utilizes agricultural raw materials to create a creative culinary product, predominantly made by women. However, it has not been managed properly according to the target market with a profit-oriented approach. The objective of this community service activity is to enhance the skills of the community, especially women, in (1) commercial production of Sambal Bakar and branding of the product based on quality standards, including brand naming and product distinctiveness, and (2) utilizing social media. The method employed in this activity includes needs assessment, implementation, and mentoring/recommendations. Data analysis follows the simultaneous 6P stages technique by Winarno & Robfiah, which comprises approach, exploration, deepening, matching, interpretation, and presentation. The results of the activity indicate that the women's community is skilled in producing the distinctive "Pawon Benjor" Sambal Bakar. Furthermore, the branding of the Sambal Bakar product as a business identity that sets it apart from competitors is achieved through brand naming and the creative and innovative distinctiveness of the product, such as using pottery for grilling. Additionally, Instagram social media is utilized in business development.